Gender and renewable energy transitions: discourses used by prominent NGOs in the United States - Pauley, Hannah, author; Stevis, Dimitris, advisor; Olofsson, Kristin, committee member; Mao, KuoRay, committee member (Colorado State University. Libraries, 2025)
This master's thesis evaluates the discourses used by prominent non-governmental organizations (NGOs) in the United States when discussing gender in connection with renewable energy transitions. In the current political environment of the United States, with a presidential administration attempting to weaken the environmental state and reduce states' rights to address issues of justice, NGOs have become important actors in advancing gender equality within energy systems. NGOs can bring attention to the gendered dimensions of energy transitions and can push governments to respond to calls for justice, but their stances on the issue have not been extensively analyzed. Building on Paula Walk's (2024) study, "From parity to degrowth: Unpacking narratives of a gender-just transition", this thesis evaluates the discourses used by prominent NGOs in the United States to provide more specific insights into the current politics of the energy transition in the United States. The analysis finds that the most common discourse used by the NGOs in the study is the opportunity discourse, aimed at ensuring that women and men benefit equally from the opportunities associated with a renewable energy transition. While this discourse is needed to increase the representation of women within the energy sector, it represents a traditional approach to gender mainstreaming, rooted in technological optimism and based on an isolated view of the climate crisis that limits opportunities for justice.
Keywords: gender; NGO; discourse; renewable energy; just transition